Impact of MS concentration and light qualities on alpine red ginger elongation and rooting in vitro - Pinheiro, Marcos Vinicius Marques; Schmidt, Alana Paula Chiavagatti; Araújo, Guilherme Masarro; Holz, Evandro; Otoni, Wagner Campos; Schmidt, Denise (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2019)
Some factors in in vitro cultivation, such as formulation of the culture medium and the quality of the light source, may vary the response of the plants in those conditions, favoring the photosynthetic metabolism obtaining more rustified plants capable of benefiting from the conditions of ex vitro cultivation. Thus, the objective was to evaluate in vitro elongation/rooting of Alpinia purpurata cv. Red Ginger under different light-emitting diodes (LEDs) and saline concentration of the MS medium. For this, previously established in vitro plants were maintained for 55 days in 550 mL glass flasks containing Carolina® substrate and MS culture medium with different salt concentrations, under LEDs qualities. The following parameters were evaluated: number of green and senescent leaves, shoot length, length of the largest root, fresh and dry mass of leaves, stem and root, root volume, photosynthetic pigments [chlorophyll a, chlorophyll b, total chlorophylls (a+b) and carotenoids (μg cm-2)], stomatal density and acclimatization percentage (after 33 days of ex vitro cultivation). After 55 days, plants grown under red LEDs and full-strength MS culture medium is indicated and promote efficient shoot length and photosynthetic pigment content, respectively. These conditions provided plants better adapted for ex vitro acclimatization. Index terms: Alpinia purpurata; light-emitting diode (LEDs); culture medium.